One visit root canal treatment using rotary instrument followed by semi-direct technique composite restoration - Lika Yodasari; Diatri Nari Ratih (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2017)
One visit root canal treatment is non-surgical conservative treatment of irreversible pulp disease or pulp necrosis. Treatment includes cleaning and shaping, sterilization, and obturation of root canal performed in one visit. The aim of this case report is to evaluate the success of one visit root canal treatment using rotary instrument followed by semi-direct composite restoration. A 23 year-old patient presented into dental hospital Faculty of Dentistry UGM to obtain treatment of leaking composite filling on his mandibular right molar that previously had been treated 1 year ago. The tooth was asymptomatic. Radiograph showed a cavity reaches the pulp and there was no periapical lesions, clinical examination showed necrosis. Patient was treated with one visit root canal treatment using rotary instrument followed by semi-direct technique of composite restoration. Five months after treatment the patient had no complaints. Radiographic examination showed no periapical lesions. One visit root canal treatment using rotary instrument followed by semiindirect technique composite restoration may be an effective treatment option when performed with case selection, proper diagnosis, aseptic work, as well as the appropriate operator’s knowledge and skills